2020
DOI: 10.1182/blood.2020007132
|View full text |Cite
|
Sign up to set email alerts
|

Leukoerythroblastosis and plasmacytoid lymphocytes in a child with SARS-CoV-2–associated multisystem inflammatory syndrome

Abstract: A 7-year-old girl with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) exposure presented with 4 days of fever, nausea, vomiting, diarrhea, and dark urine. At presentation, she was febrile (39.7°C), tachycardic, and tachypneic with normal blood pressure. Conjunctivitis, oropharyngeal erythema, cracked lips, and a distended abdomen were noted. Polymerase chain reaction testing for SARS-CoV-2 was positive. Laboratory testing showed elevated inflammatory markers, liver enzymes, and D-dimer. Two days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…A recent study by Mitra et al on LER in patients with COVID-19 disease [4] supports our present study that LER can occur in COVID-19-positive patients. A similar study by Lee and Margolskee [9] showed leukoerythroblastosis and plasmacytoid picture in a seven-year-old child with multisystem inflammatory syndrome (MIS-C). Similarly, a study on multisystem inflammatory syndrome in adults (MIS-A) in SARS-CoV-2 infection was done by Morris et al [10].…”
Section: Discussionsupporting
confidence: 51%
“…A recent study by Mitra et al on LER in patients with COVID-19 disease [4] supports our present study that LER can occur in COVID-19-positive patients. A similar study by Lee and Margolskee [9] showed leukoerythroblastosis and plasmacytoid picture in a seven-year-old child with multisystem inflammatory syndrome (MIS-C). Similarly, a study on multisystem inflammatory syndrome in adults (MIS-A) in SARS-CoV-2 infection was done by Morris et al [10].…”
Section: Discussionsupporting
confidence: 51%
“…9 In one series with 90 patients undergoing bone marrow procedures, 16 patients presented with metastatic non-hematologic malignancies and leucoerythroblastosis was seen in 43.75% of the latter. 12 In this study, maximum number of cases was seen in 21-30 years age group with male to female ratio of 1.1:1. Shubha HV et al 13 and Waghmare T et al 14 also observed maximum cases in 3 r d decade in their study with no significant sex distribution.…”
Section: Discussionmentioning
confidence: 51%
“…9 Recently, Leucoerythroblastosis has also been associated with SARS-CoV-2 infection. 11,12 Common mechanism exists in all the conditions leading to Leucoerythroblastosis: presence of stress or damage to the marrow and the evolution of areas of extramedullary hematopoiesis, where a well organised sinusoidal structure may not exist and the physiologic and physical barriers restraining immature cells may not be effective as in the marrow. 8 Though little is known about the premature release of immature cells in pathologic states, it has been reported that leucoerythroblastosis is more common when fibrosis accompanies tumour in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…This case was diagnosed with transient leukoerythroblastosis in the setting of an acute SARS-CoV-2 infection. It has been shown by a few groups, including ours, that immature erythroid and myeloid precursors are seen in peripheral smear of patients with SARS-CoV-2 infection [ 23 , 24 ]. Based on a current literature search, we believe that our case is the first study to report leukoerythroblastosis in a pregnant SCD patient with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%